Colon cancer stem cells: implications for prevention and therapy - Huang, Emina H. (2008)
The recent identification of colon cancer tumor-initiating cells adds further support to the cancer stem cell hypothesis. Ongoing basic and translational research efforts are aimed at gaining an increased understanding of the biology of these cells, as well as methods of targeting them. In addition, the relationship between colon carcinogenesis and inflammatory conditions, such as longstanding colitis and inherited syndromes, might be linked to the effect of the processes on stem cells in the colon. This review summarizes current literature on colon cancer stem cells and proposes strategies aimed at targeting these cells for colon cancer prevention and therapy.